2022
DOI: 10.3390/su14052901
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Risk Factors Affecting Urban Truck Traffic Accident Severity in Korea

Abstract: Due to increases in truck traffic, truck traffic safety has become an unavoidable societal issue in Korea. Truck traffic accidents were responsible for 24% of all traffic deaths in 2019, and the fatality rate was significantly higher than that of other forms of traffic. This study analyzes not only the driver and environmental factors, but also the traffic condition factors which are considered to contribute to the severity of truck traffic accidents, and presents practical truck safety solutions based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…e. The model indicates that the accident rate at night is much higher than that during the day, which is also mentioned in the research of Chen et al [44]. This is mainly because the driver's visibility is poor at night, and there are almost no lighting facilities on the highway except in service areas and tunnels.…”
Section: Comparative Analysis Of Factors Affecting Accident Occurrenc...mentioning
confidence: 65%
“…e. The model indicates that the accident rate at night is much higher than that during the day, which is also mentioned in the research of Chen et al [44]. This is mainly because the driver's visibility is poor at night, and there are almost no lighting facilities on the highway except in service areas and tunnels.…”
Section: Comparative Analysis Of Factors Affecting Accident Occurrenc...mentioning
confidence: 65%
“…The maximum speed, the number of lanes, and the number of road property-changing nodes were the most significant traffic condition factors. The results provided useful data for setting traffic safety policies in urban areas [58].…”
Section: Dhanyamentioning
confidence: 94%
“…In the logistics influencing area, truck traffic crashes had a higher frequency than those in the non-influencing area. 'Lane violation' and 'Signal violation' were identified as significant truck traffic crash causes [26]. Low visibility due to different reasons, such as fog, rain, and nighttime driving, was the focus of other studies that indicated that driving during the nighttime is associated with a higher crash risk due to fatigue and visibility restriction [27,28].…”
Section: Of 18mentioning
confidence: 99%